(untitled) (Damascus University Journal of agriculture sciences, 2021)
This research was conducted to compare between three sample preparation methods (dry ashing, wet ashing and microwave digestion method) prior to the determination of Lead (Pb), Cadmium (Cd), Iron (Fe) and Copper (Cu) concentrations in luncheon meat samples processed in Syria. The concentrations of trace metals were determined by using atomic absorption spectroscopy (AAS) after preparation of samples by the three mentioned methods. The results showed that the microwave digestion method was the best from the result of recovery and standard deviation for metal determination in chicken luncheon meat samples. The values of recovery for microwave digestion method were in the range of (98-101%), while they were in the range of (95-97%) for dry ashing and (95-98%) for wet ashing. RSD% values in microwave digestion method were the lowest when compare with other methods, the results were in the range of (0.02-1.03%) for microwave digestion, (0.22-3.82%) for dry ashing and (0.05- 4.07%) for wet as. hing method